GLOBAL DOMINATION OF THE DOLLAR ENDING? - Nikolic, Goran (National interest, 2023)
The paper points out that the relatively slow development of RMB as a reserve currency is taking place in parallel with the expansion of trade invoiced in the renminbi. It is argued that, even in the absence of financial liberalization, the renminbi could still become a global currency. Namely, the leading status in world trade creates the potential for creating demand and supply of renminbi. Additionally, in the same direction is working an increase in the number of central banks with which The People's Bank of China has agreements on swap lines for foreign exchange, as well as the accelerated development of the offshore Yuan market. An important moment will be the expected changes in the Chinese exchange rate regime, since the end of pegging RMB to a basket of currencies and the transition to an inflation-targeting regime could lead to a larger part of Asia following China that is using its currency more intensively. Additionally, although currently exclusively for domestic use, China's central bank's digital currency will eventually facilitate the international use of the renminbi. Consequently, it can be concluded that in the coming decades, the dollar will continue to play a predominant, but not, as it has been, an exclusive role in the international monetary order.
Keywords: Dollar; USA; China; Finance; currency; the global monetary order